Increasing utilisation of perinatal services: estimating the impact of community health worker program in Neno, Malawi - Chiyembekezo Kachimanga; Elizabeth L. Dunbar; Samuel Watson; Katie Cundale; Henry Makungwa; Emily B. Wroe; Charles Malindi; Lawrence Nazimera; Daniel Palazuelos; Jeanel Drake; Thomas Gates; Thomas van den Akker; et al. (BMC, 2020)
Abstract Background By 2015, Malawi had not achieved Millennium Development Goal 4, reducing maternal mortality by about 35% from 675 to 439 deaths per 100,000 livebirths. Hypothesised reasons included low uptake of antenatal care (ANC), intrapartum care, and postnatal care. Involving community health workers (CHWs) in identification of pregnant women and linking them to perinatal services is a key strategy to reinforce uptake of perinatal care in Neno, Malawi. We evaluated changes in uptake after deployment of CHWs between March 2014 and June 2016. Methods A CHW intervention was implemented in Neno District, Malawi in a designated catchment area of about 3100 women of childbearing age. The pre-intervention period was March 2014 to February 2015, and the post-intervention period was March 2015 to June 2016. A 5-day maternal health training package was delivered to 211 paid and supervised CHWs. CHWs were deployed to identify pregnant women and escort them to perinatal care visits. A synthetic control method, in which a "counterfactual site" was created from six available control facilities in Neno District, was used to evaluate the intervention. Outcomes of interest included uptake of first-time ANC, ANC within the first trimester, four or more ANC visits, intrapartum care, and postnatal care follow-up. Results Women enrolled in ANC increased by 18% (95% Credible Interval (CrI): 8, 29%) from an average of 83 to 98 per month, the proportion of pregnant women starting ANC in the first trimester increased by 200% (95% CrI: 162, 234%) from 10 to 29% per month, the proportion of women completing four or more ANC visits increased by 37% (95% CrI: 31, 43%) from 28 to 39%, and monthly utilisation of intrapartum care increased by 20% (95% CrI: 13, 28%) from 85 to 102 women per month. There was little evidence that the CHW intervention changed utilisation of postnatal care (− 37, 95% CrI: − 224, 170%). Conclusions In a rural district in Malawi, uptake of ANC and intrapartum care increased considerably following an intervention using CHWs to identify pregnant women and link them to care.